Kebijakan Lingkungan: Informasi Baik atau Buruk Bagi Investor? - Aldiyanto Haseng; Yayu Isyana D. Pongoliu (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the capital market reaction arising from the information contained in the announcement of environmental policies related to carbon trading among energy sector companies indexed on the Indonesia Stock Exchange. The study employs secondary data using a documentation method approach in the form of individual historical stock price data. The research sample consists of 64 energy sector companies listed and indexed on the Indonesia Stock Exchange. The research method applied is an event study to observe market responses to a specific event, with abnormal return analysis used as an indicator of market reaction. Furthermore, differences in abnormal returns before and after the event are examined using the Wilcoxon Signed Rank Test with the assistance of SPSS version 25. The results of the test indicate that the Wilcoxon Signed Rank Test reveals a significant difference in abnormal returns between the periods before and after the announcement of the environmental policy on carbon trading. These findings suggest that the market responds significantly to the policy-related information. This study is expected to contribute empirical evidence to the development of capital market research and serve as a consideration for policymakers in evaluating and refining carbon trading policies, so that efforts to reduce carbon emissions can be optimized in support of Indonesia’s goal of achieving net-zero emissions by 2030.